The lactation skill gaps of multidisciplinary paediatric healthcare professionals in the United Kingdom - LYNDSEY HOOKWAY (Journal of Human Nutrition and Dietetics, 2023)
Background: Breastfeeding is an important public health priority and may be particularly beneficial for medically complex infants and children. However, childhood illness and disability are associated with increased challenges and lower breastfeeding rates. The Baby Friendly Initiative has been shown to increase initiation of breastfeeding and improve health professional skills although as yet the standards have not been adopted in paediatrics. Previous studies have found breastfeeding knowledge gaps among paediatric nurses, and a recent systematic review highlighted insufficient lactation support, discouragement by healthcare professionals and lack of resources. The aim of this survey of UK paediatric professionals was to establish their self‐defined confidence and skills supporting breastfeeding. Methods: An online survey was developed to explore associations between level of training and staff confidence and perceived skill, to establish whether there is evidence that more training and/or higher breastfeeding training credentials improve skill. In total, 409 professionals, including paediatric doctors at all grades, paediatric nurses and allied health professionals, were included in the analysis. Results: This study identified specific skill gaps among professionals. Many healthcare professionals felt that different skills and specific training are required to support medically complex children. Several professionals noted that existing breastfeeding training focuses on establishing breastfeeding in healthy newborns rather than sick children in paediatrics. Participants were asked about 13 clinical competencies, and an aggregate skill score was calculated. Multiple univariate analysis of variance found that more extensive training and higher credentials are correlated with higher skill scores(p≤0.001), whereas type of professional was not. Conclusions: Despite this being a relatively motivated sample of healthcare professionals, the findings of this study suggest that breastfeeding skills are patchy and inconsistent, and particularly lacking when it comes to more complex clinical scenarios. This is significant, because it may mean that children who have more significant illness or medical complexity are disproportionately affected by gaps in knowledge and skill. Medically complex children encounter many barriers to optimal feeding−including absence of designated paediatric lactation staff, resources and support−and may have challenges such as low tone, higher calorie need and transitioning to the breast after ventilation or enteral feeding. Current skill gaps indicate that existing training would be insufficient, and bespoke paediatric breastfeeding training based on identified clinical challenges is thus justified.